From Representation to Presence: ‘Ilm Ḥuḍūrī and Suhrawardī’s Critique of Peripatetic Epistemology - Loekisno Choiril Warsito; Mutamakkin Billa; Hodri Hodri (Sekolah Tinggi Agama Islam Sadra, 2026)
This article explores the shift from representational to presential knowledge in Islamic epistemology by examining Suhrawardī’s concept of ‘ilm ḥuḍūrī (knowledge through presence). Drawing on his critique of the Peripatetic tradition in Ḥikmat al-Ishrāq, this article aims to examine two things: Suhrawardī’s study of the epistemological foundations of representative knowledge in the Peripatetic tradition, as well as its weaknesses in achieving the essence of the truth of knowledge. Using a qualitative, literature-based, and analytical approach, this study argues that Suhrawardī challenged the Peripatetic model—especially that developed by Avicenna—because it reduced knowledge to mental representations formed by definitions and logical reasoning. In his view, such knowledge is indirect because it relies on abstractions that cannot fully capture reality. Sensory perception is also limited, as it cannot grasp intangible or universal truths. In response, Suhrawardī developed ‘ilm ḥuḍūrī as a direct, non-discursive form of knowledge based on immediate presence. Knowledge here is not constructed through concepts or inference, but is revealed through insight (ishrāq), where the soul directly encounters reality. This shift from representation to presence reshapes how knowledge relates to existence and self-awareness. Ultimately, ‘ilm ḥuḍūrī lies at the heart of Suhrawardī’s philosophy of illumination, offering a critique of Peripatetic epistemology and a more integrated vision of knowledge, existence, and spiritual insight. Suhrawardī’s formulation of ‘ilm ḥuḍūrī as an alternative to conceptual-representational knowledge (‘ilm ḥuṣūlī).